Dampening of population cycles in voles affects small mammal community structure, decreases diversity, and increases prevalence of a zoonotic disease. Issue 14 (9th June 2017) - Ecke, Frauke; Angeler, David G.; Magnusson, Magnus; Khalil, Hussein; Hörnfeldt, Birger
Abstract: Long‐term decline and depression of density in cyclic small rodents is a recent widespread phenomenon. These observed changes at the population level might have cascading effects at the ecosystem level. Here, we assessed relationships between changing boreal landscapes and biodiversity changes of small mammal communities. We also inferred potential effects of observed community changes for increased transmission risk of Puumala virus (PUUV) spread, causing the zoonotic disease nephropatica epidemica in humans. Analyses were based on long‐term (1971–2013) monitoring data of shrews and voles representing 58 time series in northern Sweden. We calculated richness, diversity, and evenness at alpha, beta, and gamma level, partitioned beta diversity into turnover (species replacement) and nestedness (species addition/removal), used similarity percentages (SIMPER) analysis to assess community structure, and calculated the cumulated number of PUUV‐infected bank voles and average PUUV prevalence (percentage of infected bank voles) per vole cycle. Alpha, beta, and gamma richness and diversity of voles, but not shrews, showed long‐term trends that varied spatially. The observed patterns were associated with an increase in community contribution of bank vole ( Myodes glareolus ), a decrease of gray‐sided vole ( M. rufocanus ) and field vole ( Microtus agrestis ) and a hump‐shaped variation in contribution of common shrew ( Sorex araneus ). Long‐term biodiversity changes were largely related to changes in forest landscape structure. Number of PUUV‐infected bank voles in spring was negatively related to beta and gamma diversity, and positively related to turnover of shrews (replaced by voles) and to community contribution of bank voles. The latter was also positively related to average PUUV prevalence in spring. We showed that long‐term changes in the boreal landscape contributed to explain the decrease in biodiversity and the change in structure of small mammal communities. In addition, our results suggest decrease in small mammal diversity to have knock‐on effects on dynamics of infectious diseases among small mammals with potential implications for disease transmission to humans. Abstract : Long‐term decline and dampening of fluctuations in boreal small mammal populations significantly changed the structure of the small mammal community. Long‐term changes in the boreal landscape contributed to these changes. The observed decreases in richness and diversity of small mammals have important knock‐on effects on transmission risk of infectious diseases among small mammals via dilution effects.